2(-2x+3)=20+6

Simple and best practice solution for 2(-2x+3)=20+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(-2x+3)=20+6 equation:


Simplifying
2(-2x + 3) = 20 + 6

Reorder the terms:
2(3 + -2x) = 20 + 6
(3 * 2 + -2x * 2) = 20 + 6
(6 + -4x) = 20 + 6

Combine like terms: 20 + 6 = 26
6 + -4x = 26

Solving
6 + -4x = 26

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -4x = 26 + -6

Combine like terms: 6 + -6 = 0
0 + -4x = 26 + -6
-4x = 26 + -6

Combine like terms: 26 + -6 = 20
-4x = 20

Divide each side by '-4'.
x = -5

Simplifying
x = -5

See similar equations:

| 2970x(198x-178)-7921=0 | | -5t^2+40t+100=0 | | 2970(198x-178)-7921=0 | | -1.4(x-15)=2.4(x-0.5) | | 3p+2=-29 | | 2k^2-9k+11=4 | | 4(a-8)=-48 | | 3(y-2)+15=-5(y-7)-10 | | y^2=-4y-10 | | 5n+6-3n=3.7 | | 4x+3y+6z=2825 | | 72=6x+4(x-12) | | 4k+h=-2k-144 | | 4x-134+18=4x-32 | | x(x-6)= | | 6(6x-6)+6=8x-8 | | 3j+4=19 | | 7x+8-22=44-7x | | 2x^2+6x-5=85+x^2+1 | | 30(198x-178)-7921=0 | | Y+18=5y-10 | | 4+2r=10 | | 3(y-2)+15=-5(q-7)-10 | | 115=2x+7(4x-5) | | -8w-14=34 | | 4+2g=8 | | b+(-42)=(-86) | | y^2-4y-x^2+4=0 | | 15(198x-178)-7921=0 | | 4x-5=-4+6+6x-1 | | 2(12b+7)+9b-1=180-9b-1 | | Y+20=4y-15 |

Equations solver categories